2018
DOI: 10.1002/aqc.2926
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the fittest: Explanations for gadoid imbalance in heavily fished seas

Abstract: 1. Anthropogenic activities have caused the degradation of the world's ecosystems, accelerating the loss of biodiversity. In marine ecosystems, fishing has had strong impacts on fish populations and their habitats; however, not all species have responded equally to fishing pressure.2. Atlantic cod (Gadus morhua), haddock (Melanogrammus aeglefinus), and whiting (Merlangius merlangus) are of high commercial value throughout the North Atlantic.Despite having relatively similar life cycles, the state of stocks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, at present we are unsure of skate mortality within their nursery habitats. For R. undulata this is particularly important, given juveniles inhabit coastal and estuarian areas which are subject to a range of anthropogenic pressures (Elliott et al, 2018).…”
Section: The Population Dynamics Modelmentioning
confidence: 99%
“…Furthermore, at present we are unsure of skate mortality within their nursery habitats. For R. undulata this is particularly important, given juveniles inhabit coastal and estuarian areas which are subject to a range of anthropogenic pressures (Elliott et al, 2018).…”
Section: The Population Dynamics Modelmentioning
confidence: 99%
“…Evidence suggests that high fishing pressure, including bycatch in the current Nephrops fishery, has induced maturation to occur earlier and at smaller sizes in cod, haddock and whiting (Hunter et al, 2015). Baited Underwater Remote Video (BRUV) surveys around the Isle of Arran have also found that whiting recruited earlier, grew faster and were behaviorally dominant over other gadoid species, providing them with a competitive advantage (Elliott et al, 2018). Such evidence at least partly explains the present domination of small whiting in Arran's waters, and suggests that radical management interventions will be needed to restore the Firth of Clyde marine ecosystem to its more diverse and resilient former state.…”
Section: The Firth Of Clyde -A Transformed Ecosystemmentioning
confidence: 99%
“…These benefit from the mosaic of different seabed types within the MPA and the reduced disturbance in later years once trawling and dredging had been restricted (David Bailey, personal communication). These studies have revealed differences in nursery habitat use and other behaviors in the three main commercial gadoid fish species (cod, haddock, and whiting) (Elliott et al, 2017b(Elliott et al, , 2018 with evidence that cod in particular responds positively to higher benthic biodiversity and landscape heterogeneity (Elliott et al, 2017a,b). This work, which has involved over 600 camera drops at the time of this publication, provides a dataset covering the designation and protection of the wider MPA, which will allow changes to its protected features, biodiversity and ecosystem functions to be determined.…”
Section: Making the Case For And Monitoring The South Arran Mpa: 2011mentioning
confidence: 99%